Barriers to Education for the Marginalized Adult Learner - Flynn, Sarah; Brown, Jason; Johnson, Andrew; Rodger, Susan (Alberta Journal of Educational Research, 2011)
This qualitative study examines barriers to adult education by the marginalized adult learner. We adopted an inclusive approach by interviewing potential adult learners who had not participated in adult education programs due to illiteracy. Five overlapping themes related to barriers emerged and were categorized as: family values and responsibilities (i.e., cultural); the emotional effect of family poverty on participants’ lives (i.e., anger at the welfare system); disrupted school and learning experiences (i.e., multiple school changes); social exclusion and personal challenges (i.e., marginalization due to race, class); and turning points in participants’ education and hopes for the future (i.e., positive role models). Cette étude qualitative examine les obstacles à l'éducation pour adultes auxquels font face les adultes marginalisés. Nous avons adopté une approche inclusive en interviewant des adultes ayant pu participer à des programmes d'éducation pour adulte, mais qui ne l'avaient pas fait parce qu'ils étaient analphabètes. Il en a découlé cinq thèmes qui se chevauchent et qui sont liés aux obstacles. On les a catégorisés ainsi: les valeurs et responsabilités familiales (c.-à-d. culturelles); l'effet affectif de la pauvreté de la famille sur la vie des participants (par ex. la colère contre le système d'aide sociale); les expériences scolaires perturbées (c.-à-d. le changement d'école à de multiples reprises); l'exclusion sociale et des défis personnels; et les tournants décisifs dans l'éducation des participants et leurs espoirs pour l'avenir (c.-à-d. les modèles de rôle positifs).